Resazurin Microtiter Assay for Clarithromycin Susceptibility Testing of Clinical Isolates of Mycobacterium abscessus Group - Garcia de Carvalho, Natalia Fernandes; Sato, Daisy Nakamura; Pavan, Fernando R. [UNESP]; Ferrazoli, Lucilaine; Chimara, Erica (Wiley-Blackwell, 2016)
Background: Mycobacterium abscessus group has heterogeneous susceptibility pattern among species. The species is most common cause of nosocomial infections. Macrolides minimum Inhibitory concentration (MIC) determination is essential for the treatment. Methods: Thirty-six strains were randomly selected for performing Resazurin Microtiter Assay (REMA) for clarithromycin testing in comparison to MIC test according to Clinical and Laboratory Standards Institute (2011) recommendation. REMA has been used for detection of drug resistance in M. tuberculosis. Extended incubation was performed to detect induced resistance. Results: Thirty microliters of resazurin (0.01%) was added after visually taking MIC reading. Resistance was observed in 11.1% of M. bolletti and 4.8% of M. abscessus strains; and induced resistance was detected in 77.8% and 95.2% of M. bolletti and M. abscessus strains, respectively. All strains of M. massiliense were susceptible. The samples presented same MIC value both by visual reading and through resazurin. Conclusion: The present study showed 100% concordance between both readings, with REMA providing easier to read and report results benefit. This change in reading can also reflect on the MIC determination and report, improving the test. J. Clin. Lab. Anal. 30:751-755, 2016. (C) 2016 Wiley Periodicals, Inc.
Keywords: clarithromycin; Mycobacterium abscessus; resazurin microtiter assay; susceptibility testing